HERMENEUTIKA HUMANISTIK NASR HAMID ABU ZAYD: AL-QUR’AN SEBAGAI WACANA - Kusmana (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
This paper informs Nasr Hamid Abu Zayd ideas on Humanistic Hermeneutics, where it tries to put the Qur'an as a discourse, in a way of describing its hermenetical thought development context. Hermeneutical task formulation is an extension of the previous task that is still being in the spirit of reconstruction of a new reading of religious texts. Al-Qur'an as discourse claimed as an attempt upon an extension way of reading with the whole spirit of construction over again. This Heremeneutical task is potentially burden the establishment, and controversial but it is certain.